The vascular basement membrane as "soil" in brain metastasis. - Carbonell, W; Ansorge, O; Sibson, N; Muschel, R (Public Library of Science, 2009)
Brain-specific homing and direct interactions with the neural substance are prominent hypotheses for brain metastasis formation and a modern manifestation of Paget's "seed and soil" concept. However, there is little direct evidence for this "neurotropic" growth in vivo. In contrast, many experimental studies have anecdotally noted the propensity of metastatic cells to grow along the exterior of pre-existing vessels of the CNS, a process termed vascular cooption. These observations suggest the "soil" for malignant cells in the CNS may well be vascular, rather than neuronal. We used in vivo experimental models of brain metastasis and analysis of human clinical specimens to test this hypothesis. Indeed, over 95% of early micrometastases examined demonstrated vascular cooption with little evidence for isolated neurotropic growth. This vessel interaction was adhesive in nature implicating the vascular basement membrane (VBM) as the active substrate for tumor cell growth in the brain. Accordingly, VBM promoted adhesion and invasion of malignant cells and was sufficient for tumor growth prior to any evidence of angiogenesis. Blockade or loss of the beta1 integrin subunit in tumor cells prevented adhesion to VBM and attenuated metastasis establishment and growth in vivo. Our data establishes a new understanding of CNS metastasis formation and identifies the neurovasculature as the critical partner for such growth. Further, we have elucidated the mechanism of vascular cooption for the first time. These findings may help inform the design of effective molecular therapies for patients with fatal CNS malignancies.